Primary care quality and provider disparities in China: a standardized-patient-based studyResearch in context - Mian Huang; Scott Rozelle; Yiming Cao; Jian Wang; Zhang Zhang; Zhijie Duan; Shuyi Song; Sean Sylvia (Elsevier, 2024)
Summary: Background: Primary health care is the foundation of high-performing health systems. Achieving an improved primary care system requires a thorough understanding of the current quality of care among various providers within the system. As the world's largest developing country, China has made significant investments in primary care over the past decade. This study evaluates the quality of primary care across different provider types in China, offering in-sights for enhancing China's primary care system. Methods: We merged data from four standardized patient (SP) research projects to compare the quality of five major primary care providers in China: rural clinics, county hospitals, migrant clinics, urban community health cen-ters (CHCs), and online platforms. We evaluated quality of care across process quality (e.g., checklist completion), diagnosis quality (e.g., diagnostic accuracy), and case management (e.g., correct medication), employing multiple regression analyses to explore quality differences by provider type, and their associations with physician characteristics. Findings: We document a poor quality of primary care in China, with no-table disparities across different providers. CHCs emerge as relatively reliable primary care providers in terms of process quality, diagnostic accuracy, and cor-rect medication prescriptions. Online platforms outpace rural clinics, county hospitals, and migrant clinics in many areas, showcasing their potential to en-hance access to quality healthcare resources in under-resourced rural regions. We observe a positive association between the qualifications of physicians and the quality of primary care, underscoring the necessity for a greater presence of more highly qualified practitioners. Interpretation: Primary care quality in China varies greatly among providers, reflecting inequalities in healthcare access. While online platforms indicate po-tential for improving care in under-resourced areas, their high referral rates suggest they cannot completely substitute traditional care. The findings em-phasize the need for more qualified practitioners and stringent regulation to enhance care quality and reduce unnecessary treatments. Funding: No founders had a role in the study design, data collection, data analysis, data interpretation, or writing of the report. We have acknowledged this in the revised manuscript.